Global Regularity in Homogeneous Morrey-Herz Spaces of Solutions to Nondivergence Elliptic Equations with VMO Coefficients (Journal of Partial Differential Equations, 2007)
In this paper, by establishing the boundedness results of singular integral operators and linear commutators, we obtain the global regularity, in homogeneous Morrey-Herz spaces, of strong solutions to nondivergence elliptic equations with VMO coefficients.